Efficacy and safety of immune checkpoint inhibitor rechallenge in individuals with hepatocellular carcinoma - Scheiner, Bernhard; Roessler, Daniel; Phen, Samuel; Lim, Mir; Pomej, Katharina; Pressiani, Tiziana; Cammarota, Antonella; Fründt, Thorben Wilhelm; Felden, Johann von; Schulze, Kornelius; Himmelsbach, Vera; Finkelmeier, Fabian; et al. (JHEP reports, 2023)
Background & Aims - We investigated the efficacy and safety of immune checkpoint inhibitor (ICI) rechallenge in patients with hepatocellular carcinoma (HCC) who received ICI-based therapies in a previous systemic line. - Methods - In this international, retrospective multicenter study, patients with HCC who received at least two lines of ICI-based therapies (ICI-1, ICI-2) at 14 institutions were eligible. The main outcomes included best overall response and treatment-related adverse events. - Results - Of 994 ICI-treated patients screened, a total of 58 patients (male, n = 41; 71%) with a mean age of 65.0±9.0 years were included. Median systemic treatment lines of ICI-1 and ICI-2 were 1 (range, 1-4) and 3 (range, 2-9), respectively. ICI-based therapies used at ICI-1 and ICI-2 included ICI alone (ICI-1, n = 26, 45%; ICI-2, n = 4, 7%), dual ICI regimens (n = 1, 2%; n = 12, 21%), or ICI combined with targeted therapies/anti-VEGF (n = 31, 53%; n = 42, 72%). Most patients discontinued ICI-1 due to progression (n = 52, 90%). Objective response rate was 22% at ICI-1 and 26% at ICI-2. Responses at ICI-2 were also seen in patients who had progressive disease as best overall response at ICI-1 (n = 11/21; 52%). Median time-to-progression at ICI-1 and ICI-2 was 5.4 (95% CI 3.0-7.7) months and 5.2 (95% CI 3.3-7.0) months, respectively. Treatment-related adverse events of grade 3-4 at ICI-1 and ICI-2 were observed in 9 (16%) and 10 (17%) patients, respectively. - Conclusions - ICI rechallenge was safe and resulted in a treatment benefit in a meaningful proportion of patients with HCC. These data provide a rationale for investigating ICI-based regimens in patients who progressed on first-line immunotherapy in prospective trials. - Impact and implications - Therapeutic sequencing after first-line immune checkpoint inhibitor (ICI)-based therapy for advanced hepatocellular carcinoma (HCC) remains a challenge as no available second-line treatment options have been studied in immunotherapy-pretreated patients. Particularly, the role of ICI rechallenge in patients with HCC is unclear, as data from prospective trials are lacking. We investigated the efficacy and safety of ICI-based regimens in patients with HCC pretreated with immunotherapy in a retrospective, international, multicenter study. Our data provide the rationale for prospective trials investigating the role of ICI-based regimens in patients who have progressed on first-line immunotherapy.
Online verfügbar: 27. Oktober 2022, Artikelversion: 2. Januar 2023